PENAFSIRAN BUYA MAHMUD YUNUS (1361-1899) TERHADAP AYAT KAUNIYAH DALAM TAFSIR AL-QUR’AN AL-KARIM - Arya Chandra Argadinata; Ahmad Rifai, Andi Rosa (ADISAM PUBLISHER, 2024)
This study discusses the methodology of Buya Mahmud Yunus' interpretation of natural phenomena in the Tafsir Al-Qur'an Al-Karim. The interpreted methodology applied involves social and scientific-based analysis with a modern approach. Through this interpretation, Buya Mahmud Yunus tries to relate modern scientific understanding, such as the Big Bang theory with verses that explain the phenomenon of natural creation. By prioritizing openness to the development of science, his interpretation provides a deeper insight into the relationship between science and revelation, as well as integrating the local socio-cultural context. This research highlights how Buya Mahmud Yunus's interpretation not only conveys literal meaning but also combines educational values for students and the general public in studying the Qur'an in a simple and contextual form